Long‐term outcome of elderly patients (75 years or older) with hepatocellular carcinoma. Issue 9 (10th February 2014) - Hori, Maisa; Tanaka, Masatoshi; Ando, Eiji; Sakata, Masahiro; Shimose, Shigeo; Ohno, Miki; Yutani, Shigeru; Kuraoka, Kei; Kuromatsu, Ryoko; Sumie, Shuji; Sata, Michio
<x xml:space="preserve">Abstract</x> Aim The aim of this study was to evaluate the long‐term outcome of elderly patients with hepatocellular carcinoma (HCC) aged 75 years or older. Methods The study included 422 patients with HCC, who were divided into two age groups: 75 years or older (n = 140) and younger than 75 (n = 282). Outcomes were compared between the two groups. Results The number of elderly patients treated with supportive care alone (33 patients; 24%) was significantly higher than younger patients (30 patients; 11%, P < 0.01). The 1‐, 3‐, 5‐ and 7‐year overall survival rates of the elderly patients (81%, 55%, 39% and 23%, respectively) were worse than those of younger patients (85%, 64%, 49% and 36%, respectively, P = 0.042). However, the overall survival rate of the elderly group after excluding 63 patients treated with supportive care alone, was similar to that of the younger group (P = 0.615). Multivariate analysis identified age, total bilirubin levels, albumin levels, serum des‐γ‐carboxy prothrombin levels, tumor size, number of HCC nodules, vascular invasion, extrahepatic metastasis and treatment modality as independent and significant factors of overall survival. Conclusion Advanced age is a negative prognostic factor in patients with HCC due to the tendency for frequent use of conservative treatment rather than locoregional or surgical treatment.